2016
DOI: 10.3349/ymj.2016.57.3.741
|View full text |Cite
|
Sign up to set email alerts
|

Point-Connecting Measurements of the Hallux Valgus Deformity: A New Measurement and Its Clinical Application

Abstract: PurposeThe aim of this study was to investigate new point-connecting measurements for the hallux valgus angle (HVA) and the first intermetatarsal angle (IMA), which can reflect the degree of subluxation of the first metatarsophalangeal joint (MTPJ). Also, this study attempted to compare the validity of midline measurements and the new point-connecting measurements for the determination of HVA and IMA values.Materials and MethodsSixty feet of hallux valgus patients who underwent surgery between 2007 and 2011 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…It was believed that there was no signi cant difference between the two methods, but the former had a lower incidence of complications [11] . Jeong used the point-connecting method for measuring HVA and IMA, also due to consideration of the MTP joints' congruency and incongruency, which would affect the assessment of the severity of hallux valgus [12] .…”
Section: Discussionmentioning
confidence: 99%
“…It was believed that there was no signi cant difference between the two methods, but the former had a lower incidence of complications [11] . Jeong used the point-connecting method for measuring HVA and IMA, also due to consideration of the MTP joints' congruency and incongruency, which would affect the assessment of the severity of hallux valgus [12] .…”
Section: Discussionmentioning
confidence: 99%
“…It was believed that there was no signi cant difference between the two methods, but the former had a lower incidence of complications [11] . Jeong used the point-connecting method to measure the HVA and intermetatarsal angle (IMA), also considering the congruency and incongruency of the MTP joints, which would affect the assessment of the severity of hallux valgus [12] . supported…”
Section: Discussionmentioning
confidence: 99%
“…While the HVA is traditionally measured using the midline axis of the proximal phalanx and first metatarsal, Seo et al. (17) described a new method measuring the angle using three points (the most medial prominent point of the proximal phalanges in the first interphalangeal joint, the most medial prominent point of the first metatarsal head, and the most medial prominent and sclerotic point of the first metatarsal base). They suggested that it improves the reproducibility and validity of HVA measurement.…”
Section: Imaging Techniques and Measurementsmentioning
confidence: 99%
“…Seo et al. (17) also devised a similar point method and suggested that it improves the reliability of this measurement. An angle <9° is considered normal when using the traditional method with angles >9°, 11°, and 18° representing mild, moderate, and severe deformities, respectively (18).…”
Section: Imaging Techniques and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation